Legal Status of Crypto Currency in India: A critical review - Afzalur Rahman, Dr.; K. Mohamed K. Mohamed Jasim, Mr.; Ayub Khan Dawood, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Cryptocurrency is a new concept that claims to be a replacement of the fiat currency. Due to the interest of the people in the cryptocurrency around the world catch the attention of the regulatory bodies. In a different country, it is treated as different. As far as India is concerned the status of cryptocurrency is under evaluation period. This research paper tries to find the status of the cryptocurrency in the eye of law tries to define it and found that it is not a currency or legal tender as per the Indian legislation however it may be treated as goods.Â